Seedling Growth Evaluation of Rehabilitated Mangrove and Carbon Estimation of Two Types of Mangroves in Perlis, Langkat, North Sumatra - Ahmad Hisyam Pulungan; Basyuni, M; Rizka Amelia; Irvan; Astrid Fauzia Dewinta; Julia Syahriani Hasibuan; Itchika Sivaipram (Talenta Publisher, 2024)
Perlis Village is around the mangrove forest in Langkat Regency, North Sumatra, Indonesia. This village has several barren lands potentially planted with mangroves. They were considering that the livelihoods of most of the people were fishermen and mangrove crab catchers. It is necessary to plant and rehabilitate damaged mangrove forests to restore and repair the ecosystem in Perlis Village. Planting activities were carried out in locations considered suitable for planting 200 seedlings. Three transects were made to obtain vegetation analysis data and carbon content. Each transect consists of six plots in natural forest and restoration forest. When the seedlings at the planting location were 3 months old, observations were carried out again, and of the 135 plants, approximately 67.16 percent were still alive from a total of 200 seedlings planted. Carbon storage in natural forests is 69 Mg ha-1 and 41.64 Mg ha-1 in restoration forests. By enriching the methods and estimating the potential carbon stocks of natural and rehabilitated mangroves in Perlis village in the context of Indonesia's climate change mitigation strategy, it is hoped that this information has the potential to help the blue carbon research community and policymakers